Application of Effleurage Massage in Third Trimester Pregnant Women To Reduce Back Pain in the Working Area of the Karya Wanita Pekanbaru Health Center (JONAH : Journal of Nursing and Homecare, 2024)
Pregnancy is a natural and physiological process, in which women who have healthy reproductive organs who have experienced menstruation and have sexual intercourse with a man whose reproductive organs are healthy are very likely to experience pregnancy. Back pain is one of the most common discomforts felt by third trimester pregnant women during pregnancy. One of the non-pharmacological techniques in reducing back pain is the effleurage massage technique. The purpose of this effleurage massage technique is to reduce back pain in pregnant women and relax pregnant women. The method used in this scientific paper is a case study design with 2 subjects. The application is carried out in the Work Area of the Pekanbaru Women's Health Center, for 3 consecutive days 1 time with a duration of 5-10 minutes. Data analysis was performed using descriptive analysis. The results of the application showed that after the effleurage massage was carried out, there was a decrease in the back pain scale in both subjects, namely in subject 1 (Mrs.N) from a pain scale of 7 (severe pain) to a pain scale of 1 (mild pain) and in subject 2 (Mrs.R) from a pain scale of 8 (severe pain) to a pain scale of 1 (mild pain). Third trimester pregnant women are advised to do effleurage massage at least once a day to relax the body